2018
DOI: 10.1111/mmi.13914
|View full text |Cite
|
Sign up to set email alerts
|

Lipid rafts can form in the inner and outer membranes of Borrelia burgdorferi and have different properties and associated proteins

Abstract: Lipid rafts are microdomains present in the membrane of eukaryotic organisms and bacterial pathogens. They are characterized by having tightly packed lipids and a subset of specific proteins. Lipid rafts are associated with a variety of important biological processes including signaling and lateral sorting of proteins. To determine whether lipid rafts exist in the inner membrane of Borrelia burgdorferi, we separated the inner and outer membranes and analyzed the lipid constituents present in each membrane frac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 72 publications
3
48
0
Order By: Relevance
“…Our data and the data of others (24) indicate that bbk13 is constitutively expressed at high levels throughout the enzootic cycle. Consistent with the identification of BBK13 as one of the proteins associated with inner membrane lipid rafts of B. burgdorferi (28), we have shown that BBK13 is a non-surface-exposed membrane-associated protein. Overall, the inner membrane lipid rafts were found to be associated with proteins with transport and signaling functions (28), perhaps suggesting that the function of BBK13 lies within one or both of these categories.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our data and the data of others (24) indicate that bbk13 is constitutively expressed at high levels throughout the enzootic cycle. Consistent with the identification of BBK13 as one of the proteins associated with inner membrane lipid rafts of B. burgdorferi (28), we have shown that BBK13 is a non-surface-exposed membrane-associated protein. Overall, the inner membrane lipid rafts were found to be associated with proteins with transport and signaling functions (28), perhaps suggesting that the function of BBK13 lies within one or both of these categories.…”
Section: Discussionsupporting
confidence: 90%
“…Consistent with the identification of BBK13 as one of the proteins associated with inner membrane lipid rafts of B. burgdorferi (28), we have shown that BBK13 is a non-surface-exposed membrane-associated protein. Overall, the inner membrane lipid rafts were found to be associated with proteins with transport and signaling functions (28), perhaps suggesting that the function of BBK13 lies within one or both of these categories. Despite not being surface exposed, BBK13, like other bacterial SIMPL domain-containing proteins (30)(31)(32), was found to be immunogenic.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Given that bacterial MVs can fuse with the lipid rafts in eukaryotic cells, microdomains in bacterial cells may also function as the contact sites for MVs. Functional microdomains in the membrane that contain certain lipids, such as PE, CL, diacylglycerols, cholesterols, or polyisoprenoids, have been suggested in various bacteria, including both Gram-negative and Gram-positive species (Matsumoto et al, 2006;LaRocca et al, 2010LaRocca et al, , 2013López and Kolter, 2010;Toledo et al, 2018) although their compositions and structural bases remain largely unknown. PE and CL, which are inverted hexagonal phase-forming lipids, are major components of bacterial MVs, and the transition from the lamellar bilayer phase to the inverted hexagonal phase could facilitate the merging of lipids required for membrane fusion, once MVs come in contact with the cell (Powell and Marsh, 1985;Lewis and McElhaney, 1993;Kinnunen, 1996;Mondal Roy and Sarker, 2011).…”
Section: Composition and Action Mechanisms Of Omvsmentioning
confidence: 99%
“…Moreover, glycans are known to allow proteins to reorganize (or self-associate) themselves spatially on the cell surface through PCI or carbohydrate-carbohydrate interactions (CCI) [64,83] to form 'lipid rafts' [58,59,146,147]. These microdomains, or clusters of glycoproteins (lectins) [148] and glycolipids, once formed, regulate several biological functions [149][150][151][152], including immune reactions [116,153].…”
Section: Glycans Are Reactive Chemical Speciesmentioning
confidence: 99%